PERKEMBANGAN HUKUM ADMINISTRASI NEGARA DI INDONESIA - Fauzan Zakir (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
In general, its administration and formulation leads us to the administrative reality which is a milestone of the government to conduct and run its government. The law becomes the main basis in carrying out life to guarantee the principles of order and discipline so that there is order, ensuring a sense of independence, a sense of security, comfort, and order. The law is an umbrella between all types of human actions and behavior to achieve the principle of human protection. Sanctions are an important concluding part of law, also in administrative law. Generally there is no point in including obligations or prohibitions for citizens in state administrative legislation, when rules of conduct cannot be imposed by state administration (in the case where necessary). Furthermore, the implementation of a government sanction is valid as a decision (determination) which gives a burden to the parties. That brings with it the nature (nature) of sanctions.